Quality of Life of Children in Orphanages: A Study in Bamako, Mali - Ferhat Değer (Turkish Academic Research Review)

(untitled)
The Republic of Mali is among the poorest countries on both the African continent and in the world. Nearly 70% of the population resides in rural areas, and 10% lead a nomadic lifestyle. Data from the African Development Bank indicates that 48% of the population is under the age of 15, 49% falls between the ages of 15 and 64, and 3% is over 65. The fertility rate stands at 7.4 births per woman. From a sociological perspective, the concept of "quality-of-life" is often likened to lifestyle. Factors such as adequate nutrition, health conditions, educational levels, and access to cultural and developmental facilities have come to be recognized as indicators of quality-of-life. This paper delves into a field study that investigated the quality-of-life of children residing in orphanages in Mali. In-depth interviews were conducted with officials from three orphanages in Bamako, Mali's capital—comprising one privately owned and two state-owned institutions. A qualitative research approach was employed. The data obtained from these interviews were digitized using the NVivo software package. This data was then organized into nodes, creating a structured relationship between the nodes and the data. Content analysis was applied to interpret the qualitative data, with emerging concepts being categorized into nodes during the coding phase. Observations made during the interviews were duly noted. Additionally, quantitative data from sources like the African Development Bank, UNDP Human Development Index, World Health Organization, and Bulletin of Statistics were integrated to reinforce the qualitative findings. Based on the accumulated data, themes were developed in alignment with the three primary indicators of quality-of-life: 1) Physical welfare and social security, 2) Life expectancy, and 3) Opportunities for personal growth and education. The study's findings reveal that, regardless of the differences between state-owned and privately-owned orphanages, the overall quality-of-life of the children is below the expected standard across all three indicators.